Large-bore aspiration thrombectomy for the treatment of pulmonary embolism in octogenarians - Reid Masterson; Travis Pebror; Andrew Gauger; Adam William Schmitz; Sabah David Butty (CVIR Endovascular)
Abstract Purpose To evaluate outcomes in patients aged ≥ 80 years following large-bore aspiration thrombectomy (LBAT) for the treatment of pulmonary embolism (PE). Materials and methods All patients ≥ 80 years of age with PE treated via LBAT at a single center were analyzed from September 2019 – August 2024. This included the octogenarian subgroup from a recently published retrospective analysis assessing all PE patients treated with LBAT at our center between September 2019 and January 2023. The following outcomes were evaluated: technical success, change in several hemodynamic measures including pulmonary artery pressure (PAP) and right ventricle to left ventricle ratio (RV to LV ratio), length of hospital and intensive-care-unit (ICU) stay, procedure-related complications, and 7- and 30-day mortality. Results Forty-eight patients aged ≥ 80 years underwent LBAT procedures for PE. Technical success was achieved in 46 cases (95.8%). The mean reduction in mean PAP was 3.6 mmHg. The mean reduction in RV to LV ratio was -0.42. The mean length of postprocedural hospital and ICU stays were 5.7 ± 3.6 days and 1.0 ± 1.6 days, respectively. There were 2 procedural complications, 1 pulmonary vascular injury involving a pulmonary artery pseudoaneurysm and 1 decompensation involving hypotension requiring vasopressor support. There were no major bleeding complications or cardiac injuries. All-cause mortality was 2.1% (n = 1) at 7 days and 6.3% (n = 3) at 30 days post procedure. PE-related mortality was 2.1% (n = 1) at 30 days. Conclusion LBAT is a technically feasible procedure for the treatment of PE in octogenarian patients and has a favorable preliminary safety and mortality profile.